1998
DOI: 10.1016/s0893-133x(98)00039-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Olanzapine or Sertindole Treatment Results in Reduced Oral Chewing Movements in Rats Compared to Haloperidol

Abstract: Chronic haloperidol treatment typically produces late-onset, purposeless oral chewing movements in laboratory rats with a prevalence of 40 to 60%. Chronic clozapine does not produce these movements. Based on the phenomenologic and pharmacologic similarities between these rat chewing movements and human tardive dyskinesia (TD), the animal movements are often used as a model of tardive dyskinesia (TD). Here we report results of the association of oral chewing movements in rats withTraditional antipsychotics, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Details of olanzapine solution preparation have been described previously (Gao et al, 1998). The olanzapine concentration in the drinking water was initially 0.033 mg/ml; this concentration was modified according to measured daily water intake and body weight during the course of the experiment to maintain a dosage of approximately 2 mg/kg/day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of olanzapine solution preparation have been described previously (Gao et al, 1998). The olanzapine concentration in the drinking water was initially 0.033 mg/ml; this concentration was modified according to measured daily water intake and body weight during the course of the experiment to maintain a dosage of approximately 2 mg/kg/day.…”
Section: Methodsmentioning
confidence: 99%
“…The olanzapine concentration in the drinking water was initially 0.033 mg/ml; this concentration was modified according to measured daily water intake and body weight during the course of the experiment to maintain a dosage of approximately 2 mg/kg/day. This olanzapine dose and method of administration have been demonstrated to maintain rat plasma olanzapine levels in the human therapeutic range (Gao et al, 1998). Melatonin was dissolved in 100% ethanol and added to the drinking water at a final concentration of 0.4 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory rats chronically treated with the traditional antipsychotic drug haloperidol or other similar drugs gradually develop VCMs over a time course of 3-6 months (Clow et al, 1980a, b, c;Ellison et al, 1987;Glenthoj and Hemmingsen, 1989;Gao et al, 1998;Andreassen et al, 2003). Several characteristics of these movements, including aspects of their phenomenology, etiology, and pharmacology, resemble TD in humans (Tamminga et al, 1990;Waddington, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Observations with the atypical antipsychotic clozapine have led to a hypothesis that an imbalance between D 1 and D 2 receptor activity in the basal ganglia may underlie tardive dyskinesia (29). Several studies support a distinctly different D 1-4 binding profile relative to conventional neuroleptic drugs for both olanzapine and clozapine (7)(8)(9)(10)(30)(31)(32)(33)(34). Regardless, the existing data suggest at least a secondary or modulatory role for dopamine in the pathophysiology of tardive dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a model of spontaneous vacuous chewing movements has been proposed as a proxy for tardive dyskinesia. Gao et al (33) reported that olanzapine, unlike conventional neuroleptic drugs, did not induce vacuous chewing movements. In support of these preclinical data, in vivo human imaging studies have demonstrated lower D 2 striatal receptor occupancy with olanzapine than with haloperidol (34).…”
Section: Discussionmentioning
confidence: 99%